Construction of multi-solitons and multi kink-solitons of derivative nonlinear Schrödinger equations. (August 2022) - Van Tin, Phan
Abstract: We look for solutions to derivative nonlinear Schrodinger equations built upon solitons. We prove the existence of multi-solitons i.e. solutions behaving at large time as the sum of finite solitons. We also show that one can attach a kink at the begin of the sum of solitons i.e. multi kink-solitons. Our proofs proceed by fixed point arguments around the desired profile, using Strichartz estimates.